Konsep Tarbiyah Dalam Perspektif Surat Az-Zumar Pendekatan Tafsir Ijmali - Finadatul Wahidah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2019)
Educational providers, either in institution or learning process, have goals that must be achieved. Therefore, educational goals cannot be separated from the targets of the institution. Besides the urgency, the goals are able to direct the educators in running any educational activities. In Islamic concept, education is for the entire life of human. That is why the last goals of Islamic education is similar to the goals of human being. Both of them have roles as Allah's creature and khalifah fil Ardh. There are four Islamic educational goals based on QS Az-Zumar verse 9. The first goal is obedience to Allah and Rasullulah. The second one is the change for positive things. The third goal is being afraid of bad luck (azab) from Allah. The fourth one is wishing for blessings from Allah. Keyword : Islamic Education, Purpose